Pengaruh Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Vita Mandiri (Dunkin Donuts) Palembang - Kholilah, Kholilah (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT Purpose - The problem of this study was whether or not the influence of Compensation and Work Discipline on Employees’ Performance at PT Vita Mandiri Jaya (Dunkin 'Donuts) of Palembang.Design/methodology - Objective os study was for investigating the influence of Compensation and Work Discipline on Employees’ Performance at PT Vita Mandiri Jaya (Dunkin 'Donuts) of Palembang. These variables of the study were compensation, work Discipline and Employees’ Performance. In this study, samples taken by 43 respondents. Sample method used saturated sampling method. Data used in this study are primary data. Data collection techniques used questionnaires. Analysis of the data used is the qualitative and quantitative analysis with multiple linear regression analysis.Findings – The results showed that there was an effect simultaneously Compensation (X1) and Discipline Work (X2) on Employees’ Performance (Y) for Fobtained (5.233)> F table (4.08). it meant H0 was rejected and Ha accepted. There was partially the influence of Compensation (X1) on Employees’ Performance (Y) for tobtained (2.977) X1> t table (1.682) it meant H0 rejected and Ha accepted, did not influence beetwen Work Discipline (X2) on Employees’ performance (Y) for tobtained (0.377) <t table (1.682) meaning H0 was accepted and was Ha rejected.